MicroRNA-215: From biology to theranostic applications - Vychytilova-Faltejskova, Petra; Slaby, Ondrej (Molecular aspects of medicine, 2019)
MicroRNA-215 (miR-215) is one of the extensively studied microRNAs (miRNAs) in human diseases, especially in different types of cancer, where it plays various roles in the initiation and progression of tumors. There is also a high conservation of miR-215 among wide range of different species indicating that this miRNA may have vital functions that are maintained during evolution. During the last ten years, significant efforts were dedicated to uncover molecular mechanisms of miR-215 regulation and cellular functioning. In addition, miR-215 was repeatedly identified to have the causal roles in pathology of various diseases, where it may serve as a promising diagnostic, prognostic or predictive biomarker and as a therapeutic target. Here, we overview more than 150 reports focused on miR-215 to allow the synthesis of knowledge on its transcriptional and post-transcriptional regulation, and functioning in essential biological processes like cell and tissue development, cell survival, cell cycle and proliferation, cell migration and invasion, cellular microenvironment communication, and metabolism. Further, we summarized the findings on miR-215 roles in pathology of nonmalignant diseases and various types of cancer with special focus on miR-215 as a promising molecule for future development of theranostic miRNA-based approaches. Although it is difficult to evaluate the full theranostic potential of miR-215, it is probable that during the following years, an increasing number of theranostic miRNA modalities that overcome the current technological obstacles will appear, and enable the translation of miR-215 knowledge into the clinic.
Keywords: Tumor Microenvironment; Biomarker; Cell cycle; nádorové mikroprostředí; teranostická nanomedicína; lidé; regulace genové exprese u nádorů; mikro RNA; MicroRNAs; Therapeutic target; Neoplasms; Humans; Gene Expression Regulation, Neoplastic; nádory; Proliferation; Theranostic Nanomedicine; miR-215; cílená molekulární terapie; Molecular Targeted Therapy; Apoptosis